Imaging in inflammatory arthritis: progress towards precision medicine - Minopoulou, Ioanna; Kleyer, Arnd; Yalcin-Mutlu, Melek; Fagni, Filippo; Kemenes, Stephan; Schmidkonz, Christian; Atzinger, Armin; Pachowsky, Milena; Engel, Klaus; Folle, Lukas; Roemer, Frank; Waldner, Maximilian; et al. (Nature Reviews Rheumatology, 2023)
Imaging techniques such as ultrasonography and MRI have gained ground in the diagnosis and management of inflammatory arthritis, as these imaging modalities allow a sensitive assessment of musculoskeletal inflammation and damage. However, these techniques cannot discriminate between disease subsets and are currently unable to deliver an accurate prediction of disease progression and therapeutic response in individual patients. This major shortcoming of today’s technology hinders a targeted and personalized patient management approach. Technological advances in the areas of high-resolution imaging (for example, high-resolution peripheral quantitative computed tomography and ultra-high field MRI), functional and molecular-based imaging (such as chemical exchange saturation transfer MRI, positron emission tomography, fluorescence optical imaging, optoacoustic imaging and contrast-enhanced ultrasonography) and artificial intelligence-based data analysis could help to tackle these challenges. These new imaging approaches offer detailed anatomical delineation and an in vivo and non-invasive evaluation of the immunometabolic status of inflammatory reactions, thereby facilitating an in-depth characterization of inflammation. By means of these developments, the aim of earlier diagnosis, enhanced monitoring and, ultimately, a personalized treatment strategy looms closer.
CRIS-Team Scopus Importer:2023-09-29